Oltre l'Aforisma 125. Religione e religiosità nella formazione dell'uomo - Mario Gennari (Firenze University Press, 2012)
The essay, from Nietzsche's Aphorism 125, analyse the dialectic between the "objective" of religion and the "subjective" of religious. The "death of God" (or otherwise his impotence) in face of Auschwitz and of Market assigns to man the responsibility of the world: the same religious education must aspire to make men free and to respect their religious feelings.